Management of organizational development - Doroshuk, H. A. (Видавництво Львівської політехніки, 2014)
The possibility of using the organizational development management as the basis for implementing innovations within the framework of proactive management at the enterprise is justified. The subject and the object of the organizational development management are determined. Approaches to the organizational development management are analysed; the complex approach is selected. The subsystems of the organizational development management system are described. The basic principles of the organizational development management concept are determined. Обґрунтовано можливість управління організаційним розвитком як базису для втілення інновацій у межах проактивного управління на підприємстві. Визначено суб’єкт та об’єкт управління організаційним розвитком. Проаналізовано підходи до управління організаційним розвитком та вибрано комплексний підхід. Описано підсистеми системи управління організаційним розвитком. Визначено основні положення концепції управління організаційним розвитком.
Управління організаційним розвитком
Keywords: organizational development; proactive management; management of organizational development; innovative management; complex approach; organizational development management system; організаційний розвиток; проактивне управління; управління організаційним розвитком; інноваційний розвиток; комплексний підхід; система управління організаційним розвитком